(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Career guidance encompasses information, guidance and counselling services to assist in making educational, training and occupational choices. Career guidance and counselling programmes in higher educational institutions aim to provide assistance and advice to students to make them more and better informed in their future educational and career choices. It also helps the students to realize their strengths and weaknesses by instilling self-awareness, decision making skills, planning skills, personality development etc. At present there is a greater need to provide career guidance services in the college libraries.Though career guidance is a century old concept, recently it becomes an important issue world-wide in view of the changes in the economy brought about by globalization, privatization and emergence of ICT. Information is at the core of career guidance and education indeed, it tends to prevail over other guidance function.